2002
DOI: 10.1084/jem.20020519
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between BCR/ABL Oncoprotein and CXCR4 Signaling through a Src Family Kinase in Human Leukemia Cells

Abstract: Stromal-derived factor (SDF)-1 and its G protein–coupled receptor, CXCR4, regulate stem/progenitor cell migration and retention in the marrow and are required for hematopoiesis. We show here an interaction between CXCR4 and the Src-related kinase, Lyn, in normal progenitors. We demonstrate that CXCR4-dependent stimulation of Lyn is associated with the activation of phosphatidylinositol 3-kinase (PI3-kinase). This chemokine signaling, which involves a Src-related kinase and PI3-kinase, appears to be a target fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 63 publications
(105 reference statements)
8
92
0
Order By: Relevance
“…Furthermore, fractionation of SFK −/− LDBM cells into Sca-1 + Lin + and Sca-1 + Lin − cells did not reveal significant differences in the homing potential of these cells compared to WT control cells. Thus, although in vitro migration of Lyn −/− LDBM cells in response to stromal-derived factor-1 has been shown to be altered, in vivo this alteration is not sufficient to affect the homing potential of SFK −/− or Lyn −/− BM cells under the experimental conditions employed in the present study [44]. In summary, our studies highlight an essential role for Src kinases in regulating cell-intrinsic growth and engraftment of HSC/P cells and provide new insight into cytokine signaling during hematopoiesis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, fractionation of SFK −/− LDBM cells into Sca-1 + Lin + and Sca-1 + Lin − cells did not reveal significant differences in the homing potential of these cells compared to WT control cells. Thus, although in vitro migration of Lyn −/− LDBM cells in response to stromal-derived factor-1 has been shown to be altered, in vivo this alteration is not sufficient to affect the homing potential of SFK −/− or Lyn −/− BM cells under the experimental conditions employed in the present study [44]. In summary, our studies highlight an essential role for Src kinases in regulating cell-intrinsic growth and engraftment of HSC/P cells and provide new insight into cytokine signaling during hematopoiesis.…”
Section: Discussionmentioning
confidence: 62%
“…Ptasznik et al [44] recently demonstrated a biochemical interaction between CXCR4 and Lyn Src kinase in normal BM progenitors. They showed that CXCR4-dependent stimulation of Lyn kinase is associated with the activation of phosphatidylinositol 3 kinase and loss of Lyn Src kinase in BMLD cells (i.e., Lyn −/− BM cells) impairs stromal-derived factor-1-induced migration in vitro by as much as 70% compared to control cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying BCR-ABLmediated inhibition of CXCR4 function in CML cells involves the Src-related kinase Lyn. It was found that BCR-ABL constitutively activates Lyn in CML cells, resulting in Lyn becoming unresponsive to CXCL12-mediated signaling and promoting the egress of immature cells from the bone marrow (20). Importantly, it was demonstrated that TKI treatment restores CXCR4 expression and CXCR4-mediated migration toward the bone marrow niche, therefore promoting stroma-mediated resistance of CML cells to TKI (22).…”
Section: Discussionmentioning
confidence: 94%
“…Our previous work showed that the CXCR4-dependent migration of immature CD34 þ CML cells is impaired and that the integrindependent migration and adhesion in response to CXCL12 are decreased (19). Others have found that the BCR-ABL oncoprotein interferes with CXCR4-mediated signaling, and suppresses the CXCL12-induced chemotactic response of CML cells (20,21). Importantly, recent studies demonstrated that CXCR4 can be elevated by TKI treatment and may induce stroma-promoted chemoresistance (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data point to mechanisms of transformation by p210 BCR/ABL , which do not depend only on the autonomous properties of transformed cells, but also on the relationship of these cells with the microenvironment. The role of other chemokines and chemokine receptors in CML is under active investigation: CML progenitors fail to respond to CCL3 and CCL2 (Eaves et al, 1993;Wark et al, 1998), and levels and/or activity of chemokine receptors (Salgia et al, 1999;Ptasznik et al, 2002;Geay et al, 2005;Jongen-Lavrencic et al, 2005) are downregulated in p210 BCR/ABL -expressing cells, changes potentially involved in the abnormal trafficking of CML progenitors and in their release from the bone marrow. Our findings indicate that the production of some chemokines may also be impaired in p210 BCR/ABL -expressing cells and suggest that restoration of chemokine expression negatively affects leukemogenesis.…”
Section: Expression Of Ccl9/mip-1c G Iotti Et Almentioning
confidence: 99%